Succession Planning Best Practices for Large and Small Organizations - Bano, Yasmeen; Omar, Siti Sarah; Ismail, Fadillah (Mediterranean Journal of Social Sciences, 2022)
Developing potential candidates for organizational sustainability and business continuity is emerging as a priority in any organization. Every organization small or large is facing or will face challenges for the immediate future successor with the right people. Top management can create surroundings which allows leadership development with the help of succession planning internally. Succession planning is an enterprise approach that has gained a lot of interest in all organizations because of excessive demand for holding knowledge and the shortage of skilled workforce. The study has been done by using standard systematic literature review method. The current study focuses to provide comprehensive review of best succession planning practices followed by all type of organizations. The major purpose of this article is to describe the standard best practices of succession planning in any organization. This study will provide enough evidence to use succession planning as an instrument in the organizations in recruitment process, employee retention strategies and top management future development within the organization. Received: 17 September 2021 / Accepted: 14 December 2021 / Published: 5 March 2022